PENGARUH DISCOVERY LEARNING BERBANTU MEDIA AUDIOVISUAL TERHADAP PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA - Muhammad Khaza Ilfa; Sekar Dwi Ardianti; Mohammad Syafruddin Kuryanto (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2023)
The study is intended to learn the influence the discovery learning model was to assist audiovisual about the increased ability to solve the math problems of class IV students. It is conducted at Public Elementary School Klumpit 1, with a kind of quantitative research using a matode experiment of one group preposttest design. The sampling technique used in the study is the saturated sampling technique, with the number of students in the fourth class of students in the population of 10 boys and 15 girls. Pretest average value is 47.84. The posttest average is up to 80.36. The normal results of Shapiro-Wilk test that the pretest and posttest data above have sig > 0.05 with pretest data 0.054 > 0.05 and the posttest data 0.063 > 0.05 at significant levels 0.05 and n = 25, and H0 is accepted. N-gain tests, a value of 0.61 lies between 0.3 indicators 0.7 and a moderate increase in criteria. Thus it may be concluded that there is an increased ability to solve students' math problems through learning with the discovery learning model to assist audiovisual media.